Design and synthesis of DMAP-derived organocatalysts for enantioselective induction - Ó Dálaigh, Ciarán (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
The development of small organic molecules capable of mimicking enzymatic action (in an asymmetric catalysis context) is a challenge that is receiving widespread attention in contemporary organic chemistry. Herein we report the design and synthesis of a new class of chiral 4-N,N-dialkyaminopyridine acyl-transfer catalysts capable of exploiting both van der Waals (π) and H-bonding interactions to allow remote chiral information to stereochemically control the kinetic resolution of a diverse range (both aromatic and aliphatic) sec-alcohols with moderate to excellent selectivity (S = 6 - 30). A combination of optimisation, substrate screening, catalyst modification, spectroscopic and computational studies have clearly identified both hydrogen bonding and (intra as well as possibly also intermolecular) π-pyridinium- ion interactions as playing a role in enantiodiscrimination for the (S)-a,adiarylprolinol derived catalysts.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin